Inhibition of Calcitonin Gene-related Peptide (CGRP) has the Potential to Extend First-phase Insulin Secretion - Tanaka, H.; Kashiwagi, R.; Koizumi, T. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The neuropeptide calcitonin gene-related peptide (CGRP), known to have a strong vasodilation effect, has also been reported to inhibit insulin secretion. However, the physiological effect of CGRP related to insulin secretion is still unknown. Here, we evaluated the effect of whole-body CGRP inhibition by anti-CGRP antibodies in mice using an oral glucose tolerance test. CGRP has 2 isotypes, alpha-CGRP and beta-CGRP, and we confirmed the antibody used in this study inhibits function of both. Then, we evaluated the effect of CGRP inhibition on insulin secretion and discovered that CGRP inhibition lead to extend first-phase insulin secretion in an antibody dose-dependent manner and nearly plateaued at 10 mg/kg, although the effect was not so large and didn’t affect plasma glucose level. We then measured the plasma antibody concentration and it was increased depending on administration dose. So, the effect of first-phase insulin secretion extension was determined to be the result of complete inhibition of CGRP by the antibody. These results indicate that CGRP has the potential to inhibit insulin secretion and shorten first-phase insulin secretion. However the effect of CGRP inhibition was not so large at least on healthy condition, and it indicates the effect of CGRP related to insulin secretion on healthy physiological condition may be limited.
Keywords: calcitonin gene-related peptide (CGRP); oral glucose tolerance test (OGTT); insulin secretion; diabetes